When does contacting more people lessen the transmission of infectious diseases? - Mello, Bernardo A. (Frontiers in Applied Mathematics and Statistics, 2023)
A primary concern in epidemics is to minimize the probability of contagion, often resorting to reducing the number of contacted people. However, the success of that strategy depends on the shape of the dose-response curve, which relates the response of the exposed person to the pathogen dose received from surrounding infected people. If the reduction is achieved by spending more time with each contacted person, the pathogen charge received from each infected individual will be larger. The extended time spent close to each person may worsen the expected response if the dose-response curve is convex for small doses. This is the case when the expected response is negligible below a certain dose threshold and rises sharply above it. This paper proposes a mathematical model to calculate the expected response and uses it to identify the conditions when it would be advisable to reduce the contact time with each individual even at the cost of increasing the number of contacted people.